A composite pole piece and its preparation method and application

By rolling the electrode diaphragm with the electrolyte diaphragm to form a composite film, the problems of insufficient thinness and easy fracture in the prior art are solved, and more efficient battery electrochemical performance and production efficiency are achieved.

CN117790923BActive Publication Date: 2025-04-01JIANGSU QINGTAO ENERGY TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311809210.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-04-01
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

It is difficult to prepare thinner electrolyte membranes for solid-state batteries prepared by existing dry methods, and the electrolyte membrane is prone to break during the recombination process, affecting the electrochemical performance and production efficiency of the battery.

Method used

By rolling the electrode diaphragm and the electrolyte diaphragm together, the electrolyte diaphragm and the electrode diaphragm are simultaneously pressed and recombined to form a composite film, which avoids the fracture problem during thermal recombination and improves the thinness of the electrolyte membrane.

Benefits of technology

Thinner electrolyte membrane preparation is achieved, improving the electrochemical performance and production efficiency of the battery, reducing interface resistance, and enhancing rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004631112490000131
    Figure BDA0004631112490000131
  • Figure BDA0004631112490000141
    Figure BDA0004631112490000141
Patent Text Reader

Abstract

The present invention provides a composite pole piece and a preparation method and application thereof, wherein the preparation method comprises the following steps: laminating and rolling an electrode membrane and an electrolyte membrane to obtain a composite membrane; the electrode membrane and the electrolyte membrane are independently prepared by a dry method; and a current collector is compounded with the composite membrane to obtain the composite pole piece. The preparation method of the present invention rolls the electrode membrane and the electrolyte membrane prepared by the dry method together, so that the electrolyte membrane and the electrode membrane are simultaneously compressed and thinned, and are compounded together to form a composite membrane, which not only obtains a thinner electrolyte membrane, but also avoids the problem of two thinner dry-prepared membranes being broken during thermal compounding, thereby improving production quality and production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a composite pole piece and a preparation method and application thereof. Background Art

[0002] The electrodes of traditional lithium-ion batteries are usually prepared by wet method, using water or organic solvents to prepare electrode slurry for coating. Among them, organic solvents not only cause environmental pollution, but also some organic solvents such as NMP are highly hygroscopic, which will cause excessive moisture content during the preparation process, resulting in swelling of the battery during long-term cycles and rapid performance degradation. Dry preparation does not require the addition of solvents to the raw materials and can be applied to solvent-sensitive systems, such as sulfide electrolytes. Compared with the traditional slurry mixing method, it is more energy-saving, environmentally friendly and safe.

[0003] At present, solid-state batteries prepared by dry method are mainly prepared by thermally compounding separately produced positive electrode sheets, negative electrode sheets and electrolyte membranes; for example, CN 112670483A discloses a positive electrode sheet, a positive electrode plate and a solid-state battery, wherein the positive electrode plate is compounded with the positive electrode sheet and the current collector layer by hot rolling, and the solid-state battery is assembled in sequence from a positive electrode plate layer composed of a positive electrode plate, a solid electrolyte layer and a negative electrode plate layer composed of a metal lithium negative electrode.

[0004] However, the dry process is affected by the equipment precision and the electrode itself (the material is easy to stick to the roller), and it is difficult to prepare a thinner electrolyte membrane. In addition, the existing oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes are basically brittle ceramic materials with poor mechanical strength. The corresponding solid electrolyte membranes are easy to break after being thinned to a certain extent or in the subsequent process of compounding with the positive and negative electrode sheets, making it difficult to achieve continuous production. In order to have better electrical performance and energy density, the electrolyte membrane must be thin enough.

[0005] Based on the above research, it is necessary to provide a method for preparing a composite electrode, which can prepare a thinner electrolyte membrane. Summary of the invention

[0006] The object of the present invention is to provide a composite electrode sheet and a preparation method and application thereof. The preparation method rolls the electrode membrane and the electrolyte membrane together so that the electrolyte membrane and the electrode membrane are simultaneously thinned and compounded together to form a composite membrane. This not only obtains a thinner electrolyte membrane, but also avoids the problem of two thinner membranes being pulled apart during thermal compounding, thereby improving production quality and efficiency, as well as the electrochemical performance of the battery.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a composite electrode, the method comprising the following steps:

[0009] (1) laminating and rolling the electrode membrane and the electrolyte membrane to obtain a composite membrane;

[0010] The electrode membrane and the electrolyte membrane are independently prepared by a dry method;

[0011] (2) Compounding the current collector with the composite membrane described in step (1) to obtain the composite electrode.

[0012] Preferably, the thickness of the electrode membrane in step (1) is ≥ 800 μm, preferably 1000-5000 μm.

[0013] Preferably, the thickness of the electrolyte membrane in step (1) is less than 300 μm, preferably ≤100 μm.

[0014] Preferably, in step (1), the thickness ratio of the electrode membrane to the electrolyte membrane is >8, preferably 15-50.

[0015] Preferably, the compaction density of the electrode membrane in step (1) is 0.05 g / cm 3 the following.

[0016] Preferably, the compaction density of the electrolyte membrane in step (1) is 0.03 g / cm 3 the following.

[0017] Preferably, the thickness of the composite membrane in step (1) is less than 500 μm, preferably ≤ 300 μm.

[0018] Preferably, the composite membrane in step (1) comprises an electrolyte layer and electrode active material layers arranged on both sides of the electrolyte layer, and the thickness of the electrolyte layer is less than 50 μm, preferably ≤ 20 μm.

[0019] Preferably, in step (1), the ratio of the thickness of the electrode membrane to the thickness of the electrode active material layer is ≥3, preferably 5-15.

[0020] Preferably, the electrode membrane is a positive electrode membrane or a negative electrode membrane.

[0021] Preferably, the electrode membrane in step (1) is prepared by the following method:

[0022] The electrode active material, the conductive agent and the first binder are mixed and fiberized, and then pre-pressed to obtain the electrode membrane;

[0023] Preferably, the electrolyte membrane in step (1) is prepared by the following method:

[0024] The solid electrolyte powder is mixed and fiberized, and then pre-pressed to obtain the electrolyte membrane; wherein the solid electrolyte powder includes a solid electrolyte, a conductive agent and a second binder.

[0025] Preferably, the solid electrolyte powder further comprises an additive, and the amount of the additive added accounts for 1-30wt% of the weight of the second binder.

[0026] Preferably, the additive includes any one or a combination of at least two of sodium carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.

[0027] Preferably, the fiberization method includes any one of air milling, high-speed stirring, mechanical fusion or twin-screw extrusion, or a combination of at least two of them.

[0028] Preferably, the electrode active material includes a positive electrode active material or a negative electrode active material.

[0029] Preferably, the positive electrode active material includes any one of layered oxides, spinel active materials or olivine-type active materials, or a combination of at least two thereof.

[0030] Preferably, the negative electrode active material includes any one of graphite, silicon, silicon-graphene, silicon-aluminum alloy, tin-based materials, graphene, asphalt carbon microspheres, activated carbon, carbon fiber, graphene, carbon nanotubes, carbon aerogel, transition metal oxides, conductive polymers, lithium-containing compounds, hard carbon materials or soft carbon materials, or a combination of at least two thereof.

[0031] Preferably, the solid electrolyte includes any one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a hydride solid electrolyte, a boride solid electrolyte or a nitride solid electrolyte, or a combination of at least two thereof.

[0032] Preferably, the conductive agent comprises any one or a combination of at least two of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers;

[0033] Preferably, the first binder and the second binder independently include any one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyvinyl chloride, polystyrene, polyoxymethylene, polycarbonate, polyamide, acrylic plastic, polysulfone, polyphenylene ether or carboxymethyl cellulose, or a combination of at least two thereof.

[0034] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0035] (1) mixing and fiberizing an electrode active material, a conductive agent and a first binder, and then pre-pressing the mixture to obtain an electrode membrane;

[0036] The solid electrolyte, the conductive agent and the second binder are mixed and fiberized, and then pre-pressed to obtain an electrolyte membrane;

[0037] (2) laminating and rolling the electrode membrane described in step (1) and the electrolyte membrane described in step (1) to obtain a composite membrane;

[0038] The thickness of the electrode membrane is ≥800 μm, and the compaction density is 0.05 g / cm 3 Below; the thickness of the electrolyte membrane is less than 300μm, and the compaction density is 0.03g / cm 3 Below; the thickness ratio of the electrode membrane to the electrolyte membrane is>8;

[0039] The composite membrane has a thickness of less than 500 μm, and comprises an electrolyte layer and electrode active material layers disposed on both sides of the electrolyte layer, the electrolyte layer has a thickness of less than 50 μm, and a ratio of the thickness of the electrode membrane to the electrode active material layer is ≥3;

[0040] (3) Compounding the current collector with the composite membrane sheet of step (2) to obtain the composite electrode sheet.

[0041] In a second aspect, the present invention provides a composite pole piece, which is prepared by the preparation method described in the first aspect.

[0042] In a third aspect, the present invention provides a battery, comprising the composite electrode as described in the second aspect.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The present invention rolls the electrode membrane and the electrolyte membrane together, thereby increasing the overall thickness of the rolled membrane and facilitating further thinning of the two membranes. In addition, since the electrode membrane has sufficient mechanical strength, when rolled together, the solid electrolyte membrane can obtain stable mechanical support and connection support from the electrode membranes on both sides, thereby reducing the possibility of breakage during further thinning, so that a thinner electrolyte membrane can be obtained under the same rolling process as that of preparing the electrolyte layer alone.

[0045] (2) The present invention rolls the electrode membrane and the electrolyte membrane together to composite the two, thereby avoiding the situation where two thin dry-process prepared membranes are crushed or broken due to the strong pressure or traction of the equipment during the hot composite feeding process; at the same time, it also reduces the preparation process of rolling the electrode membrane and the electrolyte membrane separately. In the present invention, the rolling of the electrode membrane and the rolling of the electrolyte membrane are combined together, saving the process steps of separate rolling, which is convenient for improving production efficiency;

[0046] (3) The preparation method of the present invention enables the electrolyte membrane and the electrode membrane to be composited during pre-pressing and forming the membrane, and the composite surfaces are more tightly composited, so that the interface resistance of the battery is smaller, the ion transfer rate is increased, and the rate performance of the battery is improved.

[0047] (4) The present invention adds a one-dimensional additive to the electrolyte powder. On the one hand, it can increase the plasticity of the electrolyte membrane and improve its ductility. On the other hand, the one-dimensional structure of the additive can provide tensile support for the electrolyte membrane along the membrane surface, thereby reducing the risk of fracture of the electrolyte membrane during the calendering process. DETAILED DESCRIPTION

[0048] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0049] In a first aspect, the present invention provides a method for preparing a composite electrode, the method comprising the following steps:

[0050] (1) laminating and rolling the electrode membrane and the electrolyte membrane to obtain a composite membrane;

[0051] The electrode membrane and the electrolyte membrane are independently prepared by a dry method;

[0052] (2) Compounding the current collector with the composite membrane described in step (1) to obtain the composite electrode.

[0053] Since the traditional dry preparation process is to first compound the electrode membrane with the current collector and then compound it with the electrolyte membrane, the pre-pressing and subsequent rolling of the electrolyte membrane and the electrode membrane separately not only cannot prepare a thinner electrolyte membrane with excellent mechanical properties, but also there is a problem of the electrolyte membrane breaking when loading; the present invention rolls the electrode membrane and the electrolyte membrane together, which increases the overall thickness of the rolled membrane. Since the electrode membrane and the electrolyte membrane both have a certain ductility, they will be stretched after rolling together, so that when the electrolyte layer is prepared separately, a thinner electrolyte membrane can be obtained under the same rolling process, and the two thinner membranes are avoided from being pulled apart due to the strong traction force of the equipment during the hot composite loading process, which facilitates continuous production, ensures production quality, improves production efficiency, reduces interface resistance, and improves battery rate performance.

[0054] In some specific embodiments, the thickness of the electrode membrane in step (1) is ≥800 μm, for example, it can be 1000 μm, 2000 μm, 3000 μm, 4000 μm or 5000 μm, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 1000-5000 μm.

[0055] In some specific embodiments, the thickness of the electrolyte membrane in step (1) is less than 300 μm, for example, it can be 200 μm, 100 μm, 80 μm, 60 μm or 40 μm, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably ≤100 μm.

[0056] In order to ensure the ductility of the membrane during co-rolling, the present invention preferably uses a thicker electrode membrane and a thicker electrolyte membrane, so as to obtain a thinner composite electrode sheet with higher mechanical strength.

[0057] In some specific embodiments, the thickness ratio of the electrode membrane and the electrolyte membrane in step (1) is greater than 8, for example, it can be 10, 15, 20, 30, 40 or 50, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 15-50.

[0058] In some specific embodiments, the compaction density of the electrode membrane in step (1) is 0.05 g / cm 3 Below, for example, it can be 0.05g / cm3, 0.01g / cm 3 , 0.005g / cm 3 , 0.0025g / cm 3 , 0.001g / cm 3 or 0.0005g / cm 3 , but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0059] In some specific embodiments, the compaction density of the electrolyte membrane in step (1) is 0.03 g / cm 3 Below, for example, it can be 0.02 g / cm 3 , 0.01g / cm 3 , 0.005g / cm 3 , 0.0025g / cm 3 , 0.001g / cm 3 or 0.0005g / cm 3 , but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0060] In order to facilitate rolling of the electrode membrane and the electrolyte membrane, the present invention preferably uses the electrode membrane and the electrolyte membrane with the above compaction density.

[0061] In some specific embodiments, the thickness of the composite membrane in step (1) is less than 500 μm, for example, it can be 400 μm, 300 μm, 200 μm, 100 μm or 50 μm, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably ≤300 μm.

[0062] In some specific embodiments, the composite membrane in step (1) includes an electrolyte layer and an electrode active material layer arranged on both sides of the electrolyte layer. The thickness of the electrolyte layer is less than 50 μm, for example, it can be 30 μm, 20 μm, 15 μm, 10 μm or 5 μm, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably ≤20 μm.

[0063] In the present invention, the electrode membrane and the electrolyte membrane are combined into a composite membrane after rolling together. In the composite membrane, the electrolyte layer can be thinned to ≤40 μm, meeting the battery's requirements for electrical performance and energy density for thinner electrolyte membranes.

[0064] In some specific embodiments, the electrode membrane is a positive electrode membrane or a negative electrode membrane.

[0065] In some specific embodiments, the electrode membrane in step (1) is prepared by the following method:

[0066] The electrode active material, the conductive agent and the first binder are mixed and fiberized, and then pre-pressed to obtain the electrode membrane.

[0067] In some specific embodiments, the electrolyte membrane in step (1) is prepared by the following method:

[0068] The solid electrolyte powder is mixed and fiberized, and then pre-pressed to obtain the electrolyte membrane; wherein the solid electrolyte powder includes a solid electrolyte, a conductive agent and a second binder.

[0069] In some specific embodiments, the solid electrolyte powder also includes an additive, and the amount of the additive added accounts for 1-30wt% of the weight of the second binder, for example, it can be 5wt%, 10wt%, 20wt% or 30wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] The present invention adds a one-dimensional additive to the electrolyte powder, which can increase the plasticity of the electrolyte membrane and improve its ductility on the one hand, and on the other hand, the one-dimensional structure of the additive can provide tensile support for the electrolyte membrane along the membrane surface direction, reducing the risk of fracture of the electrolyte membrane during the calendering process.

[0071] In some specific embodiments, the additive includes any one or a combination of at least two of sodium carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.

[0072] In some specific embodiments, the fiberization method includes any one or a combination of at least two of air milling, high-speed stirring, mechanical fusion or twin-screw extrusion;

[0073] In some specific embodiments, the electrode active material includes a positive electrode active material or a negative electrode active material.

[0074] The present invention has no particular limitation on the type of positive electrode active material. Any known positive electrode active material can be used in the present invention without violating the concept of the present invention.

[0075] In some specific embodiments, the positive electrode active material includes any one or a combination of at least two of layered oxides, spinel active materials or olivine-type active materials. Typical but non-limiting combinations include a combination of layered oxides and spinel active materials, or a combination of layered oxides and olivine-type active materials.

[0076] Exemplarily, the layered oxide includes LiCoO 2 、LiNi x Mn y Co 1-x-y O 2 (where 0≤x≤1, 0≤y≤1), LiNi 1-x-y Co x Al y O 2 (where 0≤x≤1 and 0≤y≤1), LiNi x Mn 1-x O 2 (where 0≤x≤1) or Li 1+x MO 2 (wherein, 0≤x≤1, M includes any one of Mn, Ni, Co or Al or a combination of at least two); the spinel active material includes LiMn 2 O 4 and / or LiNi x Mn 2-x O 4 (0<x<2); the olivine type active material includes LiMPO4 (wherein M includes any one of Fe, Ni, Co or Mn or a combination of at least two thereof).

[0077] The present invention has no particular limitation on the type of negative electrode active material. Any known negative electrode active material can be used in the present invention without violating the concept of the present invention.

[0078] In some specific embodiments, the negative electrode active material includes any one or a combination of at least two of graphite, silicon, silicon-graphene, silicon-aluminum alloy, tin-based materials, graphene, pitch carbon microspheres, activated carbon, carbon fibers, graphene, carbon nanotubes, carbon aerogels, transition metal oxides, conductive polymers, lithium-containing compounds, hard carbon materials or soft carbon materials. Typical but non-limiting combinations include a combination of graphite and silicon, or a combination of pitch carbon microspheres and activated carbon.

[0079] The present invention does not specifically limit the solid electrolyte, and all known solid electrolytes can be used in the present invention.

[0080] In some specific embodiments, the solid electrolyte includes any one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a hydride solid electrolyte, a boride solid electrolyte or a nitride solid electrolyte, or a combination of at least two of them. Typical but non-limiting combinations include a combination of an oxide solid electrolyte and a sulfide solid electrolyte, or a combination of a halide solid electrolyte and a hydride solid electrolyte.

[0081] In some specific embodiments, the conductive agent includes any one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers, or a combination of at least two of them. Typical but non-limiting combinations include a combination of superconducting carbon and acetylene black, or a combination of carbon black and Ketjen black.

[0082] In some specific embodiments, the first binder and the second binder independently include any one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyvinyl chloride, polystyrene, polyoxymethylene, polycarbonate, polyamide, acrylic plastic, polysulfone, polyphenylene ether or carboxymethyl cellulose, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of polytetrafluoroethylene and polyvinylidene fluoride, or a combination of polypropylene and polyvinyl chloride.

[0083] As a preferred embodiment, the preparation method comprises the following steps:

[0084] (1) mixing and fiberizing an electrode active material, a conductive agent and a first binder, and then pre-pressing the mixture to obtain an electrode membrane;

[0085] The solid electrolyte, the conductive agent and the second binder are mixed and fiberized, and then pre-pressed to obtain an electrolyte membrane;

[0086] (2) laminating and rolling the electrode membrane described in step (1) and the electrolyte membrane described in step (1) to obtain a composite membrane;

[0087] The thickness of the electrode membrane is ≥800 μm, and the compaction density is 0.05 g / cm 3 Below; the thickness of the electrolyte membrane is less than 300μm, and the compaction density is 0.03g / cm 3 Below; the thickness ratio of the electrode membrane to the electrolyte membrane is>8;

[0088] The composite membrane has a thickness of less than 500 μm, and comprises an electrolyte layer and electrode active material layers disposed on both sides of the electrolyte layer, the electrolyte layer has a thickness of less than 50 μm, and a ratio of the thickness of the electrode membrane to the electrode active material layer is ≥3;

[0089] (3) Compounding the current collector with the composite membrane of step (2) to obtain the composite electrode. In a second aspect, the present invention provides a composite electrode, which is prepared by the preparation method of the first aspect.

[0090] In a third aspect, the present invention provides a battery, comprising the composite electrode as described in the second aspect.

[0091] Example 1

[0092] This embodiment provides a method for preparing a composite electrode, the method comprising the following steps:

[0093] (1) mixing and fiberizing an electrode active material, a conductive agent and a first binder, wherein the electrode active material is LiNi 0.8 Mn 0.1 Co 0.1 O 2 , the conductive agent is carbon black, the first binder is polyvinylidene fluoride, and then pre-pressing is performed to obtain an electrode membrane;

[0094] The solid electrolyte, the conductive agent and the second binder are mixed and fiberized, wherein the solid electrolyte is LLZO, the conductive agent is carbon black, and the second binder is polyvinylidene fluoride, and then pre-pressed to obtain an electrolyte membrane;

[0095] Wherein, the fiberization method is air jet milling;

[0096] (2) laminating the electrode membrane described in step (1) and the electrolyte membrane described in step (1), and then rolling them together to obtain a composite membrane;

[0097] The thickness of the electrode membrane is 2520 μm and the compaction density is 0.01 g / cm 3 The thickness of the electrolyte membrane is 280 μm and the compaction density is 0.01 g / cm 3 ; The thickness ratio of the electrode membrane to the electrolyte membrane is 9;

[0098] (3) thermally compounding the aluminum foil with the composite membrane of step (2) to obtain the composite electrode sheet, wherein the composite membrane comprises an electrolyte layer and electrode active material layers disposed on both sides of the electrolyte layer;

[0099] The thickness of the composite membrane is 210 μm, and the thickness of the electrolyte layer is 47 μm.

[0100] Example 2

[0101] This embodiment provides a method for preparing a composite electrode sheet, which is the same as that of Embodiment 1 except that in step (1), the thickness of the electrode membrane is 2250 μm, the thickness of the electrolyte membrane is 150 μm, and the thickness of the electrolyte layer changes accordingly after rolling.

[0102] Example 3

[0103] This embodiment provides a method for preparing a composite electrode sheet, which is the same as that of Embodiment 1 except that in step (1), the thickness of the electrode membrane is 2500 μm, the thickness of the electrolyte membrane is 100 μm, and the thickness of the electrolyte layer changes accordingly after rolling.

[0104] Example 4

[0105] This embodiment provides a method for preparing a composite electrode sheet, which is the same as that of Embodiment 1 except that in step (1), the thickness of the electrode membrane is 4000 μm, the thickness of the electrolyte membrane is 80 μm, and the thickness of the electrolyte layer changes accordingly after rolling.

[0106] Example 5

[0107] This embodiment provides a method for preparing a composite electrode sheet, which is the same as that of Embodiment 1 except that in step (1), the thickness of the electrode membrane is 5000 μm, the thickness of the electrolyte membrane is 83 μm, and the thickness of the electrolyte layer changes accordingly after rolling.

[0108] Example 6

[0109] This embodiment provides a method for preparing a composite electrode sheet, which is the same as that of Embodiment 1 except that in step (1), the thickness of the electrode membrane is 900 μm, the thickness of the electrolyte membrane is 60 μm, and the thickness of the electrolyte layer changes accordingly after rolling.

[0110] Example 7

[0111] This embodiment provides a method for preparing a composite electrode sheet. In the preparation method, except that the electrode active material in step (1) is graphite material, the compaction density of the electrode membrane is 0.045 g / cm 3 The compacted density of the electrolyte membrane is 0.02g / cm 3 Except that the thickness of the electrolyte layer after rolling changes accordingly, the rest is the same as Example 1.

[0112] Example 8

[0113] This embodiment provides a method for preparing a composite electrode. The preparation method is the same as that of Embodiment 1 except that in step (1), when preparing a solid electrolyte membrane, an additive (hydroxyethyl cellulose) accounting for 10 wt% of the weight of the second binder is added to change the thickness of the electrolyte layer after rolling.

[0114] Comparative Example 1

[0115] This comparative example provides a method for preparing a composite electrode sheet, which is the same as Example 1 except that in step (1), the thickness of the electrode membrane is 130 μm, the thickness of the electrolyte membrane is 100 μm, and the thickness of the electrolyte layer changes accordingly after rolling.

[0116] Comparative Example 2

[0117] This embodiment provides a method for preparing a composite electrode sheet, which is the same as that of Embodiment 1 except that in step (1), the thickness of the electrode membrane is 650 μm, the thickness of the electrolyte membrane is 130 μm, and the thickness of the electrolyte layer changes accordingly after rolling.

[0118] The thickness ratio of the electrode membrane and the electrolyte membrane, the thickness of the electrode membrane, the thickness of the electrolyte membrane, and the thickness of the electrolyte layer after rolling of the above embodiments and comparative examples are shown in the following table:

[0119] Table 1

[0120]

[0121]

[0122] From the above table we can see that:

[0123] (1) The present invention first prepares the electrode membrane and the electrolyte membrane by a dry method, and then rolls them together, which can make the solid electrolyte layer in the composite electrode thinner and ensure that the electrolyte membrane and the electrode membrane are rolled at the same time, and the rolling effect is high; it can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that the thickness of the electrode membrane and the electrolyte membrane, as well as the thickness ratio, will affect the thickness of the electrolyte layer after rolling.

[0124] (2) It can be seen from Example 1 and Examples 2-6 that the thickness of the electrode membrane and the electrolyte membrane of the present invention will affect the thickness of the electrolyte layer after rolling, and the thickness ratio of the electrode membrane and the electrolyte membrane is preferably greater than 8; It can be seen from Example 1 and Example 7 that the compaction density of the electrode membrane and the electrolyte membrane of the present invention will also affect the thickness of the electrolyte layer after rolling; It can be seen from Example 1 and Example 8 that adding a one-dimensional additive to the electrolyte powder can enhance the plasticity of the electrolyte membrane and improve its ductility.

[0125] In summary, the present invention provides a composite electrode sheet and a preparation method and application thereof. The preparation method rolls the electrode membrane and the electrolyte membrane together so that the electrolyte membrane and the electrode membrane are simultaneously thinned and compounded together to form a composite membrane. This not only can obtain a thinner electrolyte membrane, but also avoids the problem of two thinner membranes being pulled apart during thermal compounding, thereby improving the production quality and efficiency, as well as the electrochemical performance of the battery.

[0126] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite pole piece, characterized in that: The preparation method comprises the following steps: (1) Laminating and rolling the electrode membrane and the electrolyte membrane to obtain a composite membrane; The electrode membrane and the electrolyte membrane are independently prepared by a dry method; The thickness of the electrode membrane is ≥800 μm, and the thickness of the electrolyte membrane is <300 μm; (2) Compounding the current collector with the composite membrane of step (1) to obtain the composite electrode.

2. The preparation method according to claim 1, characterized in that: The thickness of the electrode membrane in step (1) is 1000-5000 μm.

3. The preparation method according to claim 1, characterized in that: The thickness of the electrolyte membrane in step (1) is ≤100 μm.

4. The preparation method according to claim 1, characterized in that: In step (1), the thickness ratio of the electrode membrane to the electrolyte membrane is greater than 8.

5. The preparation method according to claim 4, characterized in that: In step (1), the thickness ratio of the electrode membrane to the electrolyte membrane is 15-50.

6. The preparation method according to claim 1, characterized in that: The compaction density of the electrode membrane in step (1) is 0.05 g / cm 3 the following.

7. The preparation method according to claim 1, characterized in that: The compacted density of the electrolyte membrane in step (1) is 0.03 g / cm 3 the following.

8. The preparation method according to claim 1, characterized in that: The thickness of the composite membrane in step (1) is less than 500 μm.

9. The preparation method according to claim 8, characterized in that: The thickness of the composite membrane in step (1) is ≤300 μm.

10. The preparation method according to claim 1, characterized in that: The composite membrane of step (1) comprises an electrolyte layer and electrode active material layers arranged on both sides of the electrolyte layer, and the thickness of the electrolyte layer is less than 50 μm.

11. The preparation method according to claim 10, characterized in that: The thickness of the electrolyte layer is ≤20 μm.

12. The preparation method according to claim 10, characterized in that: In step (1), the ratio of the thickness of the electrode membrane to the thickness of the electrode active material layer is ≥3.

13. The preparation method according to claim 12, characterized in that: In step (1), the ratio of the thickness of the electrode membrane to the thickness of the electrode active material layer is 5-15.

14. The preparation method according to claim 1, characterized in that: The electrode membrane is a positive electrode membrane or a negative electrode membrane.

15. The preparation method according to claim 1, characterized in that: The electrode membrane in step (1) is prepared by the following method: The electrode active material, the conductive agent and the first binder are mixed and fiberized, and then pre-pressed to obtain the electrode membrane.

16. The preparation method according to claim 1, characterized in that: The electrolyte membrane in step (1) is prepared by the following method: The solid electrolyte powder is mixed and fiberized, and then pre-pressed to obtain the electrolyte membrane; wherein the solid electrolyte powder includes a solid electrolyte, a conductive agent and a second binder.

17. The preparation method according to claim 16, characterized in that: The solid electrolyte powder further includes an additive, and the additive is added in an amount of 1-30wt% of the weight of the second binder.

18. The preparation method according to claim 17, characterized in that: The additive includes any one of sodium carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose or a combination of at least two thereof.

19. The preparation method according to claim 16, characterized in that: The solid electrolyte includes any one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a hydride solid electrolyte, a boride solid electrolyte or a nitride solid electrolyte, or a combination of at least two thereof.

20. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing and fiberizing the electrode active material, the conductive agent and the first binder, and then pre-pressing to obtain an electrode membrane; The solid electrolyte, the conductive agent and the second binder are mixed and fiberized, and then pre-pressed to obtain an electrolyte membrane; (2) stacking and rolling the electrode membrane described in step (1) and the electrolyte membrane described in step (1) to obtain a composite membrane; The thickness of the electrode membrane is ≥800 μm, and the compaction density is 0.05 g / cm 3 Below; the thickness of the electrolyte membrane is less than 300μm, and the compaction density is 0.03g / cm 3 Below; the thickness ratio of the electrode membrane to the electrolyte membrane is>8; The composite membrane has a thickness of less than 500 μm, and comprises an electrolyte layer and electrode active material layers disposed on both sides of the electrolyte layer, the electrolyte layer has a thickness of less than 50 μm, and a ratio of the thickness of the electrode membrane to the electrode active material layer is ≥3; (3) Compounding the current collector with the composite membrane of step (2) to obtain the composite electrode.

21. A composite pole piece, characterized in that: The composite pole piece is prepared by the preparation method as described in any one of claims 1-20.

22. A battery, characterized in that: The battery comprises the composite pole piece as claimed in claim 21.

Citation Information

Patent Citations

  • Positive plate, positive plate and solid-state battery

    CN112670483A

  • All-solid-state battery cell, preparation method thereof and solid-state battery

    CN111883855A

  • Solid electrolyte and application thereof

    CN114976212A

  • Composite electrode plate, preparation method thereof and lithium ion battery

    CN117096281A

  • Composite lithium-supplementing negative plate as well as preparation method and application thereof

    CN117790698A